2020
DOI: 10.1057/s41599-020-00656-y
|View full text |Cite
|
Sign up to set email alerts
|

Is there gender bias in research grant success in social sciences?: Hong Kong as a case study

Abstract: Despite growing attention to gender disparities in higher education, women in academia still receive less research funding and recognition. Previous research on this gender gap has focused on biomedical, science, technology, engineering, and mathematics in the West—relatively silent on social sciences and Asia. This study examined how well staff gender, submission rate, success rate, and amount per award could predict annual changes in the number and amount of grant funding for academic years 2015/2016–2020/20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…The results did not clearly show the important role of work environment factor in gender differences in scientific achievement, using performance assessment by leaders, as stated in the last hypothesis. As stated elsewhere (VASS, 2008;Nguyen Kim Hoa, 2010;Yip et al, 2020), a fair and accurate assessment by leaders will motivate researchers to become more passionate and active in research, thereby contributing more to science. Results from this study, however, showed that the assessment of the institute's leaders did not make a significant difference in the scientific outputs of female and male researchers.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The results did not clearly show the important role of work environment factor in gender differences in scientific achievement, using performance assessment by leaders, as stated in the last hypothesis. As stated elsewhere (VASS, 2008;Nguyen Kim Hoa, 2010;Yip et al, 2020), a fair and accurate assessment by leaders will motivate researchers to become more passionate and active in research, thereby contributing more to science. Results from this study, however, showed that the assessment of the institute's leaders did not make a significant difference in the scientific outputs of female and male researchers.…”
Section: Discussionmentioning
confidence: 97%
“…Fair performance assessment of researchers by leaders was an important factor in promoting effort and enthusiasm among researchers (VASS, 2008;Nguyen Kim Hoa, 2010). Yip et al (2020) identified good practices for promoting gender equality in scientific research, such as institutional policies that reduce the academic burden of women raising young children and caring for elderly parents. Studies have suggested that when mothers were given supportive structural opportunities, their productivity was at the same rate as childless women (Henley, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A major issue in the sociology of science and in debate within the scientific community is whether gender makes a difference, for example, in access to research funding (Yip et al 2020, Ranga et al 2012, Bornmann et al 2007 or research output (Berenbaum 2019, Kunadt et al 2014, Larivière et al 2013, Cole & Zuckermann 1984. Particularly during this pandemic, there have been concerns that women, on average, face greater burdens than their male counterparts due to more involvement in domestic care work and home schooling (Else 2020, Kibbe 2020, King & Fredericksen 2021, Rusconi, Netz & Solga 2020.…”
Section: Professors Adapt Fastermentioning
confidence: 99%